Never never [compact disc, unabridged] - Patterson, James, 1947-; Fox, Candice (Patterson, James, 1947- Detective Harriet Blue, 2017)
When Sydney police department sex crimes detective Harriet Blue is called into her boss's office, she can't imagine it could be to tell her that her brother is the prime suspect in the brutal murders of three women. Shocked and in denial, Harry is transferred to Perth to avoid the media exposure this case will attract. Harry is sent into the outback--the never never--to investigate the disappearance of mine worker Danny Carter. The mining town is a seedy place, full of money and immoral ways to spend it. As Harry delves deeper into the murky lives of these miners, she finds that Danny isn't the first to go missing.